Development of bottled sweet sour sauce - Paras, Antonio S.; Arcellana, Mayi Y. (1978.)
This is a study of the feasibility of producing bottled sweet sour sauce. Cornstarch at 1.91%, 2.29% and 3.81% levels and CMC at 0%, 0.2% and 0.4% levels were incorporated into a chosen recipe. Analysis was made of the soluble solids (SS), titratable acidity (TA), SS/TA, pH and consistency of the finished products. A descriptive scorecard analyzing color, texture, flavor, consistency and general acceptability of the products was presented to a panel of ten judges. Results of the sensory evaluation analyzed by ANOVA and the Duncan's Multiple Range Test show that there are statistical differences among the three samples with respect to flavor, consistency and general acceptability at the 5% level of significance. Based on the overall sensory and objective evaluations, the sample containing 2.92% cornstarch and 0.4% CMC was judged as the most acceptable.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Sauces; Sweet sour sauce